2015
DOI: 10.1016/j.taap.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole increases the efficacy of a soluble epoxide hydrolase inhibitor in a PGE2 induced pain model

Abstract: Epoxyeicosatrienoic acids (EETs) are potent endogenous analgesic metabolites produced from arachidonic acid by cytochrome P450s (P450s). Metabolism of EETs by soluble epoxide hydrolase (sEH) reduces their activity, while their stabilization by sEH inhibition decreases both inflammatory and neuropathic pain. Here, we tested the complementary hypothesis that increasing the level of EETs through induction of P450s by omeprazole (OME), can influence pain related signaling by itself, and potentiate the anti-hyperal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Helander et al demonstrated that 16 h after radioactive omeprazole administration, the radioactivity of the stomach was 100 times higher than blood [48]. The concentration of TPPU in plasma was similar to the previously published literature [4]. Like TPPU, omeprazole appears to show excellent target occupancy.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Helander et al demonstrated that 16 h after radioactive omeprazole administration, the radioactivity of the stomach was 100 times higher than blood [48]. The concentration of TPPU in plasma was similar to the previously published literature [4]. Like TPPU, omeprazole appears to show excellent target occupancy.…”
Section: Resultssupporting
confidence: 81%
“…Diclofenac is known to be metabolized by uridine 5′-diphosphoglucuronosyl transferase 2B7, cytochrome P450s (CYP) 2C9 and 3A4 [44]. Omeprazole is known to increase activity of CYP3A4 [4]. We measured the concentration of DCF and omeprazole to evaluate if omeprazole treatment increased the metabolism of DCF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). This increase in epoxide-containing lipids may result from increased biosynthesis by induced P450 enzymes (Goswami et al, 2015), whereas the increase caused by TPPU is from reduced metabolism. Levels of other quantified metabolites were not altered significantly and are presented in Supplemental Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…An anti-inflammatory role of omeprazole in decreasing ulcer has been reported (Biswas et al, 2003). The reduction of ulcers by OME is attributable, at least in part, to induction of key P450 oxidases, thus increasing the biosynthesis of anti-inflammatory epoxy fatty acids (Goswami et al, 2015). Thus, the efficacy of TPPU, which stabilizes epoxy fatty acids, on prevention of NSAID-induced ulcers is not surprising.…”
Section: Discussionmentioning
confidence: 97%